How Digital Payment And Social Media Marketing Affect Purchase Decisions Of Subang Culinary SME Customer, Indonesia - Apriandi, Devy; Najmudin, Najmudin; Karnowati, Nandang Bekti; Prakoso, Fajar Adi (Publisher Cv. Inara, 2023)
This research is an empirical study to see the relationship between the application of digital payment media and digital marketing for small and medium enterprises, especially in the culinary sector in the city of Subang. Why is this research being carried out in Subang, because there are not many small and medium entrepreneurs in the culinary sector in the city of Subang who have implemented digital payments and digital marketing in their businesses. The data in this research uses primary data obtained from 121 questionnaires to culinary business customers who make digital payments and search for information digitally before making a purchase. From the results of data processing, it is known that digital payments have a significant effect on purchasing decisions in small and medium businesses in the culinary sector with a T-count score of 6,357, and marketing using social media also has a significant effect with a T-count value of 6,609, and together digital payments and marketing social media has a significant effect with an F count of 114,804